Difficulties and Social Marginalization of Native English- Speaking Professors in University English Programs - 홍성연; 김현진 (영어교육, 2024)
This study examines the challenges faced by native English-speaking professors who teach general English courses in Korean universities, specifically focusing on the issue of social marginalization. Data were collected through online surveys and interviews. The findings indicate that these professors view themselves as a non-mainstream group within university faculties, often experiencing exclusion from decision-making processes and professional development opportunities, primarily due to language barriers. Moreover, cultural differences and structural discrimination exacerbate these challenges. Although the respondents did not report significant difficulties related to student education and exhibited a strong sense of efficacy in teaching English, some lacked sufficient understanding of the institutional curriculum. To address these issues, this study suggests that, for foreign professors to fully demonstrate their expertise in English education and foster a sense of belonging within the university community, they should be granted the authority and responsibility to participate in curriculum improvement research, along with administrative assistance.
Keywords: native English-speaking professors; social marginalization; cultural alienation; general English